factores que afectan la rentabilidad de la franquicia Disensa el turco - Garcia Limones, María Alexandra (2017)
When talking about profitability we refer to the result of the productivity process. If the projected results are positive profits are generated and the company or business would be fulfilling the objective; otherwise, if the result is negative, losses would be generated, so there would be a need to review marketing strategies to increase demand (Castaño & Jurado, 2016).